Sistem Informasi Administrasi Arsip Elektronik Surat Menyurat Di Kantor Kecamatan Ngusikan Kabupaten Jombang - Izzatul Umami (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
This research was designed Information System Service Administration Correspondence village level in order to improve the quality of service for the villagers. The benefit of this research is expected to help simplify the process of service correspondence residence at the village level. In this research that used to design the information system of this letter is SDLC (System Development Life Cycle). SDLC covers research implementation steps from the beginning till the end. The conclusion of this research result is with the presence of Information System Service Administration Correspondence, the process of Administration Correspondence can run faster, precise and effective. The arrangement of correspondence reports can be done more quickly, thoroughly and neatly.